A Technical Nuance to Avoid Lumbar Five Radiculopathy with Anterior Lumbar Fusion and Posterior Instrumentation. (25th March 2021) - Neal, Matthew T.; Kalani, Maziyar A.; Lyons, Mark K.
Abstract : The anterior lumbar interbody fusion (ALIF) is a well-established procedure used to treat a multitude of spinal pathologies. When performed at the L5-S1 level, the ALIF is often supplemented with posterior pedicle screw and rod fixation. Because the interbody device can restore disk and foraminal height, one benefit of the ALIF procedure is indirect neural decompression in the spinal canal and neural foramina. If the contour of the posterior rod is not matched to the exact position of the tulip heads on the pedicle screws, spondylolisthesis can be introduced, leading to foraminal stenosis and nerve compression. This concern is particularly germane when the posterior instrumentation is placed percutaneously without any direct foraminal decompression. In this report, we describe a patient who had an L4-S1 ALIF, resulting in new L5-S1 retrolisthesis and worsening L5 radiculopathy. Technical nuances and avoidance strategies are discussed.